Interventions to improve ergonomics in the operating theatre: A systematic review of ergonomics training and intra-operative microbreaks. (July 2020) - Koshy, Kiron; Syed, Habib; Luckiewicz, Andrew; Alsoof, Daniel; Koshy, George; Harry, Lorraine
Abstract: Musculoskeletal occupational injury is prevalent within the surgical community. This is a multi-factorial issue, but is contributed to by physical posture, environmental hazards and administrative deficiency. There is growing awareness of this issue, with several behavioural, educational and administrative techniques being employed. The literature on this topic is, however, sporadic and difficult to access by healthcare practitioners. The aim of this systematic review was to evaluate the literature on the current interventions used to minimise musculoskeletal occupational injury in surgeons and interventionalists. This review will focus on administrative and human factor interventions, such as intra-operative microbreaks and ergonomics training. Highlights: Musculoskeletal occupational injury is highly prevalent in surgeons and is well reported in the literature. No systematic reviews currently exist on interventions used to reduce musculoskeletal injuries in surgeons and interventionalists. In this study we carry out a systematic review to evaluate current interventions to minimise musculoskeletal in surgeons. This review is foccused on the use of ergonomics training and intra-operative microbreaks.